2018
DOI: 10.31878/ijcbr.2018.43.13
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Inflammatory Disease (Pid): A Cross Sectional Prospective Study at a Tertiary Care Centre

Abstract: Introduction : Pelvic inflammatory disease (PID) is an infection of the upper part of the female reproductive system namely the uterus, fallopian tubes, and ovaries, and inside of the pelvis. Objective: to find out the clinical profile of PID in a tertiary care centre. Methods: This was a cross sectional, descriptive study conducted at the Department of Obstetrics and Gynaecology, during period from January to December2016. Total 200 patients complaining of lower abdominal pain, vaginal discharge & having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Majority of PID patients(66.6%) had parity between 2-5; 16.7% had parity one and similar % of women were nulliparous, which is accordance with the studies of Ahmed S.et al (Ahmed et al, 2017) and Shinde SA.et al, (SA et al, 2018) who reported incidence of PID between 2-5 parity in 56% and 58% patients respectively.…”
Section: Number Of Live Births and Abortionsupporting
confidence: 89%
“…Majority of PID patients(66.6%) had parity between 2-5; 16.7% had parity one and similar % of women were nulliparous, which is accordance with the studies of Ahmed S.et al (Ahmed et al, 2017) and Shinde SA.et al, (SA et al, 2018) who reported incidence of PID between 2-5 parity in 56% and 58% patients respectively.…”
Section: Number Of Live Births and Abortionsupporting
confidence: 89%